Optimalisasi Infrastruktur Jaringan dengan Teknologi Fiber Optic di PT. Sinar Nusantara Industries - Wiyana Baitul Izza, Khomsah (Journal Information Technology Trends (JITRENDS), 2024)
PT. Sinar Nusantara Industries is a manufacturing company that produces famous building materials. One of the important divisions in the company's operations is the Information Technology (IT) division that is responsible for network infrastructure. Currently, the company uses UTP cables for the network, but the distant inter-building distance leads to connectivity instability. To address this problem, the study proposes replacing the UTP cable with fiber optics from the server room to the finished product warehouse (GPJ) to improve the network infrastructure at PT. Sinar Nusantara Industries. This research uses the PPDIOO method (Prepare, Plan, Design, Implement, Operate, Optimize) to ensure each step is done in a structured manner. Research results show that the use of fiber optic cables increases network speeds from 100 Mbps to 300-500 Mbps and improves the stability and reliability of remote connections. The implementation also utilizes fast connectors to facilitate connectivity without splicing, making it more effective. Thus, this move is expected to improve network performance and security in PT. Sinar Nusantara Industries